2012
DOI: 10.1111/j.1095-8649.2012.03318.x
|View full text |Cite
|
Sign up to set email alerts
|

Walleye Sander vitreus and smallmouth bass Micropterus dolomieu interactions: an historic stable‐isotope analysis approach

Abstract: The carbon (δ(13) C) and nitrogen (δ(15) N) values of Sander vitreus scales differed pre and post-introduction in treatment lakes among years following the introduction of Micropterus dolomieu. No difference of δ(13) C and δ(15) N in S. vitreus scales was found in control lakes where M. dolomieu were not introduced. In treatment lakes, S. vitreus δ(15) N increased and δ(13) C decreased. No relationship was found between S. vitreus and M. dolomieu abundance in the two treatment lakes. Size structure of S. vitre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Smallmouth bass are voracious predators that have been found to out‐compete cold‐water predators, such as lake trout, for energetically rewarding littoral prey fish (Vander Zanden et al ., ). The effect of smallmouth bass expansion on coolwater fish is less clear because there are large geographic regions of habitat overlap, and evidence that suggests co‐existence is possible when prey availability is high (Johnson & Hale, ; Frey et al ., ; Galster et al ., ). Individual lake studies have often yielded mixed results: Johnson & Hale () found that smallmouth bass invasions reduced walleye populations in three of four Minnesota lakes, while Kempinger & Carline () found that walleye introductions in smallmouth bass lakes caused bass to decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smallmouth bass are voracious predators that have been found to out‐compete cold‐water predators, such as lake trout, for energetically rewarding littoral prey fish (Vander Zanden et al ., ). The effect of smallmouth bass expansion on coolwater fish is less clear because there are large geographic regions of habitat overlap, and evidence that suggests co‐existence is possible when prey availability is high (Johnson & Hale, ; Frey et al ., ; Galster et al ., ). Individual lake studies have often yielded mixed results: Johnson & Hale () found that smallmouth bass invasions reduced walleye populations in three of four Minnesota lakes, while Kempinger & Carline () found that walleye introductions in smallmouth bass lakes caused bass to decline.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Galster et al . () analysed stable carbon and nitrogen isotope changes in walleye before and after smallmouth bass colonization in four lakes and found that walleye tissue became more nitrogen‐rich and carbon‐negative after colonization, indicating a shift in consumption of benthic to pelagic prey. It is possible that this shift occurs because smallmouth bass display competitive territorial behaviour in the presence of other predators, which could exclude walleye from near‐shore prey resources (Wuellner et al ., ; Galster et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These standard ellipse areas are a bivariate measure of the distribution of individuals in trophic space; each ellipse encloses~40% of the data and, therefore, represents the core dietary niche of that species in that river (Jackson et al, 2011(Jackson et al, , 2012. The second method was to use the stable isotope data within generalized linear models (GLMs) in which fish length was a covariate, as per Galster et al (2012). The full methodology for calculating these metrics is available in Jackson et al (2011Jackson et al ( , 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Biological invasion, as a pervasive and costly environmental problem, has changed the interspecies relationships, trophic levels of organisms, and habits of native species; it poses a serious threat to biodiversity and native food webs and ecosystems (Qiu and Chen 2009;Vander Zanden et al 1999;Wesner and Belk 2015). For example, after the invasion of smallmouth bass (Micropterus dolomieu) in glacial lakes, the feeding habitats of native species Walleye (Sander vitreus) was displaced from a littoral to a pelagic area (Galster et al 2012).…”
Section: Introductionmentioning
confidence: 99%